The development of the chondrocranium of Melopsittacus undulatus - Kock, Johannes M. de(Johannes Marthinus),1929- (Stellenbosch : Stellenbosch University, 2012)
Dissertations (D. Phil.) -- University of Stellenbosch, 1984.